A PHILOSOPHICAL PERSPECTIVE ON IDENTITY RECOGNITION AS A STRATEGY FOR BULLYING MITIGATION IN EDUCATION: THE CASE OF PEMATANGSIANTAR CITY - Hutauruk, Ahmad Fakhri; Ginting, Andres M.; Asnewastri, Asnewastri; Chandra, Satria; Damanik, Anggi Safitri; Damanik, Hana Pertiwi; Purba, Nur Ainun (Program Pascasarjana UIN Sumatera Utara, 2025)
The phenomenon of identity-based bullying in the multicultural educational environment of Pematangsiantar City reflects a complex issue that extends beyond individual behavior and is closely linked to the failure of educational institutions to substantively recognize student identity diversity. This study aims to explore how a philosophical approach to identity recognition can be applied as a more fundamental and sustainable bullying mitigation strategy. Employing a qualitative case study design, data were collected through in-depth interviews with students, teachers, and educational staff, complemented by participant observations and analysis of school policy documents. Data analysis was conducted using Miles and Huberman’s techniques, which include data reduction, data display, conclusion drawing, and verification through credibility, dependability, transferability, and confirmability tests. The findings reveal that identity recognition remains primarily administrative, often neglecting psychosocial dimensions, thereby fostering identity-based bullying in the form of social exclusion, verbal bullying, and symbolic domination by majority groups. The limited integration of educational philosophy into learning processes further amplifies identity homogenization within classrooms. In conclusion, the philosophical approach to identity recognition offers a strategic contribution to strengthening inclusive education based on social justice, capable of sustainably mitigating bullying in multicultural educational settings.